THE IMPORTANCE OF THE TERTIARY SECTOR IN THE ECONOMIC DEVELOPMENT OF KERALA - R.Rakesh (SMART Journal of Business Management Studies, 2009)
Among the three sectors of economy, the tertiary sector of Kerala has played a crucial role so far in generating revenue and employment opportunities. Though the State Government and State agencies are responsible for promoting and developing the main segment of manufacturing industries sector, the progress has been tardy or dismal in the recent years. The primary/agriculture sector has been stagnating for years together. The IT sector is likely to put up a greater show than hitherto, with the expansion and development programmes now envisaged. But there is considerable scope for developing the tertiary sector, particularly trade, commerce, and tourism-related activities to promote employment generation and to improve the general economy of the State.